Isolation and Synthesis of Pulmonarins A and B, Acetylcholinesterase Inhibitors from the Colonial Ascidian Synoicum pulmonaria - Tadesse, Margey; Svenson, Johan; Sepcič, Kristina; Trembleau, Laurent; Engqvist, Stig Olov Magnus; Andersen, Jeanette Hammer; Jaspars, Marcel; Stensvåg, Klara; Haug, Tor (Journal of Natural Products, 2014)
This document is the Accepted Manuscript version of a Published Work that appeared in final form in Journal of natural products , copyright © American Chemical Society after peer review and technical editing by the publisher. To access the final edited and published work see https://doi.org/10.1021/np401002s . Pulmonarins A and B are two new dibrominated marine acetylcholinesterase inhibitors that were isolated and characterized from the sub-Arctic ascidian Synoicum pulmonaria collected off the Norwegian coast. The structures of natural pulmonarins A and B were tentatively elucidated by spectroscopic methods and later verified by comparison with synthetically prepared material. Both pulmonarins A and B displayed reversible, noncompetitive acetylcholinesterase inhibition comparable to several known natural acetylcholinesterase inhibitiors. Pulmonarin B was the strongest inhibitor, with an inhibition constant ( K i) of 20 μM. In addition to reversible, noncompetitive acetylcholinesterase inhibition, the compounds displayed weak antibacterial activity but no cytotoxicity or other investigated bioactivities.